Michael Oakeshott and the Cambridge School on the history of political thought - Thompson, Martyn P. (Routledge, 2019)
This book is a critique of Cambridge School Historical Contextualism as the currently dominant mode of history of political thought, drawing upon Michael Oakeshott's analysis of the logic of historical enquiry. While acknowledging that the early Cambridge School work represented a considerable advance towards genuinely historical histories of political thought, this work identifies two major historiographical problems that have become increasingly acute. The first is general: an insufficiently rigorous understanding of the key concept of "pastness" necessarily presupposed in historical enquiry of all kinds. The second is specific to histories of political thought: a failure to do justice to the varieties of past political thinking, especially differences between ideology and philosophy. In addressing these problems, the author offers a comprehensive account of the history of political thought that establishes the parameters not just of histories of ideological thinking but also of the much disputed character of histories of political philosophy. Since rethinking history of political thought in Oakeshottian terms requires resisting current pressures to turn history into the servant of currently felt needs, the book offers a sustained defence of the cultural value of modernist historical enquiry against its opponents. An important work for political theorists, historians of political thought and those researching intellectual history, the philosophy of history and proposed new directions in contemporary historical studies
Keywords: Oakeshott, Michael Joseph -- 1901-1990; Politische Philosophie; Political science / History; POLITICAL SCIENCE / Essays; POLITICAL SCIENCE / Government / General; POLITICAL SCIENCE / Government / National; POLITICAL SCIENCE / Reference; POLITICAL SCIENCE / General; POLITICAL SCIENCE / History & Theory